Influence of Landuse Patterns on Otamiri River, Owerri and Urban Quality of Life - Johnbosco, E. Umunnakwe; Nnaji, A.O. (Pakistan Journal of Nutrition, 2011)
Research was conducted on the impact of landuse patterns in the pollution of Otamiri river to ascertain the environmental quality of life of the city dwellers. Water and sediment samples in Otamiri river were obtained from locations closest to landfill, mechanical workshop village and sand and gravel mine. Samples were subsequently subjected to standard analytical procedures. The ranges of the result for the physicochemical parameters analyzed include pH (5.28-5.63), temperature (27.3-28.2oC), Conductivity (123-203 μS/cm), turbidity (6.4-16.3 NTU), DO (1.9-2.1 mg/l), BOD (30.00-39.50 mg/l), TSS (2.0-2.9 mg/l), total hardness (40.5-61.2 mg/l), phosphate (3.45-6.99 mg/l), Nitrate (0.5-3.0 mg/l), Sulphate (5.07-10.0 mg/l), Lead (0.02-0.60 mg/l). Result of the analysis showed that for all sampled points, the values of some variables exceeded the safe limits of WHO standards. The increased Lead concentration in the sediment, low value of dissolved oxygen and high acidity shows that landuse patterns along the Otamiri watershed deteriorated its quality, rendered it unfit and posed a health risk to Owerri residents. Consequently these activities should be zoned out of their present areas of operation to secure a better quality of life for the city dwellers.